EXPLORATION OF CARDIOPROTECTIVE AND ANTIOXIDANT ACTION OF BILIRUBIN IN ISOPRENALINE-INDUCED ISCHEMIA MODEL OF MALE WISTAR ALBINO RATS - BAREJIA, ASIF; CR, ACHARYA; SHAH, AASHAL; PATEL, ANKIT; NAVADIYA, VIPUL (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Ischemic heart disease is one of the leading causes of death worldwide. Bilirubin, an endogenous product of heme catabolism, has remarkable antioxidant properties. This study was planned with an aim to evaluate cardioprotective potential of bilirubin in isoprenaline (ISO)- induced rat myocardial ischemia model. Methods: In this study, a total of 24 adult male Wistar albino rats (200–250 g) were divided into four groups of six rats each. Groups I, III, and IV, respectively, received distilled water (10 mL/kg bw), bilirubin (40 mg/kg bw), and bilirubin (60 mg/kg bw) intraperitoneally (i.p.) for 21 days. Along with that, Groups III and IV received ISO (85 mg/kg bw) subcutaneously (s.c.) on 20th and 21st day. Group II received ISO (85 mg/kg bwi. p.) on 20th and 21st day. After 24 h of ISO administration, rats were sacrificed and biochemical and histopathological parameters were assessed. These parameters were evaluated: Cardiac biomarkers-lactate dehydrogenase (LDH) and creatine kinase (CK-MB) and antioxidant-glutathione reductase (GR). Isolated heart specimens were processed for light microscopy. Results: Administration of bilirubin in Groups III and IV significantly prevented ISO-induced elevation of CK-MB and LDH levels as compared to Group II. Furthermore, there is a significant increase in the levels of GR in Groups III and IV compared to Group II. These changes were significantly higher in Group IV (high dose) compared to Group III (low dose). Light microscopic findings of the myocardium in bilirubin-treated group revealed a well preserved normal morphology of cardiac muscle with minimal evidence of myocardial injury as compared to ISO-treated hearts. Conclusion: Pre-administration with bilirubin is protective against ISO-induced myocardial infarction. This beneficial effect is most likely due to its antioxidant property. This study may trigger interest toward the use of bilirubin as a cardioprotective agent in myocardial infarction.